PERKEMBANGAN PERUNDANG-UNDANGAN HUKUM KELUARGA MUSLIM DI MESIR ( STUDI WASIAT WAJIBAH DI MESIR) - Ishak Tri Nugroho (Familia: Jurnal Hukum Keluarga, 2020)
The long history of reforming Islamic Family Law in the Muslim world began in the 20th century when Turkey became the first Muslim country to pioneer this reform. These reforms greatly influenced the reform of Islamic family law in Egypt and provided a more forward-looking color compared to what was previously done, the impetus for reform and reform of Islamic law in Egypt came from within the Islamic tradition itself and from outside the Islamic tradition. In addition to reforming family law in general, Egypt has also reformed the concept of inheritance law regarding wajibat for orphan grandchildren, which actually does not discuss this matter in classical books. Egypt regulates the issue of compulsory wills in the Egyptian Law, namely Law no. 71 of 1946 concerning inheritance, Egypt introduced a new concept in terms of inheritance for orphaned grandchildren who are usually considered as dzawil arham who are prevented from obtaining inheritance, so they are now entitled to inheritance by using the mandatory will. The concept of wills, mandatory, for inheritance for orphaned grandchildren does not exist in classical jurisprudence, and it appears that Egypt is trying to reform the law by inventing new laws or rechtsvinding, in order to find a solution to the inheritance problems that occur in Egypt.